Effect of Processing Methods on Quality of Soymilk - Tunde-Akintunde, T.Y.; Souley, A. (Pakistan Journal of Nutrition, 2009)
Soymilk is one of the easiest ways to add soyprotein, a high quality protein, to the human diet because it doesn’t alter the taste of food. It is a highly nutritious drink and must be prepared in such an easy way that the quality is maintained. Soymilk was processed using 5 methods including delayed filtration, hot extraction, cold extraction, soaking and blanching, potash and sodium bicarbonate processing methods. The highest protein content was between 3.05% for delayed filtration and 2.23% for soaking in potash. The sensory properties of the soymilk increased with decrease in nutritional quality indicating that methods which increase sensory properties of soymilk by reducing its beany flavour have lower nutritional qualities.